Paradigma Good Governance Menuju Shared Governance Melalui Reformasi Birokrasi dan Inovasi Pelayanan Publik. - Hayat Hayat (Universitas Muhammadiyah Ponorogo, 2020)
The purpose of this paper is to describe the concepts of good governance and shared governance within the framework of the Indonesian political system. This has an important connection with public service as a realization of political policy. The problem of public services is still a challenge in improving good governance. The paradigm of good governance continues to develop according to the demands and needs of society. The method used is through a theoretical and basic study of theory. This paradigm has led to shared governance. Meanwhile, bureaucratic reform has become an important agenda that must continue to be escorted to the lowest level. To improve quality, optimize better performance, and professionals need service innovation. Public service innovation through experience learning as a concrete step in maximizing the potential of the apparatus. This innovation aims to improve the performance of the apparatus through education, training, and the development of self-potential oriented to the values of experience and practice as self-actualization in the performance of public services.